Designing a Hybrid Learning Model for Diverse Educational Needs - Mustofa, Muhammad; Costa, Tiago; Silva, Pedro (Journal International Inspire Education Technology, 2024)
The rapid shift towards digital learning has highlighted the need for flexible and inclusive educational models that address diverse learner needs. Hybrid learning, which combines traditional face-to-face instruction with online learning, offers a solution to bridge the gap between accessibility and personalized learning. This research aims to design a hybrid learning model tailored to meet the varying educational needs of students from different backgrounds, learning preferences, and technological capabilities. A qualitative approach was employed, utilizing case studies from schools and universities that have implemented hybrid learning. Interviews with educators, administrators, and students were conducted to gather insights into the strengths and challenges of hybrid learning environments. Data was also collected from surveys to analyze student engagement and learning outcomes in hybrid settings. The findings indicate that a well-designed hybrid learning model can increase student engagement, foster personalized learning experiences, and provide greater flexibility in accessing educational resources. However, challenges such as digital divide issues, technological limitations, and the need for teacher training were also identified. The study highlights the importance of integrating support mechanisms for students and educators to maximize the effectiveness of hybrid learning. In conclusion, the research underscores the potential of hybrid learning to meet diverse educational needs, provided that key challenges such as technology access and educator readiness are addressed. The findings provide valuable insights for educators and policymakers looking to implement or enhance hybrid learning models in various educational settings.